GAMIFICATION IN FOREIGN LANGUAGE CLASSROOMS: ENHANCING ENGAGEMENT AND RETENTION - Nurqulova Oydinabonu Sirojiddin qizi (TALABALAR ILMIY KONFERENSIYASI "TILSHUNOSLIK MASALALARI – YOSH TADQIQOTCHILAR NIGOHIDA", 2025)
This article presents a critical and evidence-based overview of how gamification enhances foreign language instruction. It synthesizes data from peer-reviewed studies and applies established theoretical frameworks to evaluate the role of digital games and point-based systems in promoting vocabulary acquisition and classroom participation.